Evolving Landscape of Antibody Drug Conjugates in Lymphoma. Issue 6 (November 2022) - Prakash, Rishab; Subbiah, Vivek; Iyer, Swaminathan P.
Abstract: Despite the curative potential of autologous transplantation and chimeric antigen receptor T cells in lymphoma, many patients are ineligible, or their disease progresses after these treatments. In this context, antibody drug conjugates (ADCs) have demonstrated very promising efficacy in lymphomas. Antibody drug conjugates are monoclonal antibodies covalently linked to a cytotoxic drug. Because of its highly specific targeting abilities and powerful killing effects, it has become a promising technology for developing anticancer drugs in recent years. The US Food and Drug Administration has approved 14 ADCs since Mylotarg (gemtuzumab ozogamicin) entered the market in 2000. With advances in the design of ADCs, their efficacy and safety have moved in tandem, and many novel ADCs have gained growing interest. Three ADCs, brentuximab vedotin, polatuzumab vedotin, and loncastuximab tesirine, have been approved for treating lymphoma. The rapidly evolving ADC arsenal for treating relapsed or refractory lymphoma offers many choices. The article reviews the history and general mechanism of action of ADCs. This is followed by a discussion of the molecular aspects of their key components and their mechanisms of influence on their design and function. Finally, we review up-to-date clinical data of the approved and emerging targets of ADCs in lymphoma.